Women's mental health in the perinatal period according to migrant status: the French representative ELFE birth cohort. (22nd February 2018) - El-Khoury, Fabienne; Sutter-Dallay, Anne-Laure; Panico, Lidia; Charles, Marie-Aline; Azria, Elie; Van der Waerden, Judith; Melchior, Maria
Abstract: Background: Mental health problems in the perinatal period are common. We examined associations between different categories of migrant status and region of origin in relation to mental health during pregnancy and at 2 months post-partum. Methods: We analyzed data from the French nationally representative Etude Longitudinale Française depuis l'Enfance birth cohort ( n = 17 988). Migrant status was divided into five categories: 'majority population', 'descendants with one migrant parent', 'descendants with two migrant parents', 'naturalized migrant' and 'non-naturalized migrant women'. Multivariate logistic regression models were implemented to examine associations between migrant status and mental health outcomes: persistent psychological difficulties during pregnancy as well as mother's depression and poor self-reported health at 2 months post-partum. Results: After adjusting for covariates, migrant status was not associated with psychological difficulties during pregnancy. Descendants of migrants had comparable mental health to the majority population. Non-naturalized migrant women were more likely to experience depression (odd's ratio (OR)= 1.66, 95%confidence interval (CI): 1.27, 2.20) and poor self-reported health (OR = 1.45, 95%CI: 1.06, 1.98) during the post-partum period. The region of origin was associated with post-partum health independently of migrant status, such that women from Africa and Turkey were most likely to have depression or poor self-rated health. Conclusion: First, but not second, generation migrant women appear to have high levels of mental health difficulties during the post-partum period. Women from North Africa, Sub-Saharan Africa, and Turkey have higher levels of distress than those from other regions. In particular, non-naturalized migrant appear to be a vulnerable group; they may disproportionately face stressors that increase their risk for post-partum depressive symptoms.